![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\dfrac{4^5+4^5+4^5+4^5}{3^5+3^5+3^5+3^5}\cdot\dfrac{6^5+6^5+6^5+6^5+6^5+6^5}{2^5+2^5+2^5+2^5+2^5+2^5}=2^x\)
\(\Leftrightarrow2^x=\dfrac{4^5}{3^5}\cdot\dfrac{6^5}{2^5}=4^5=2^{10}\)
=>x=10
b: \(\left(x-1\right)^{x+4}=\left(x-1\right)^{x+2}\)
\(\Leftrightarrow\left(x-1\right)^{x+2}\left[\left(x-1\right)^2-1\right]=0\)
\(\Leftrightarrow x\left(x-1\right)^{x+2}\cdot\left(x-2\right)=0\)
hay \(x\in\left\{0;1;2\right\}\)
c: \(6\left(6-x\right)^{2003}=\left(6-x\right)^{2003}\)
\(\Leftrightarrow5\cdot\left(6-x\right)^{2003}=0\)
\(\Leftrightarrow6-x=0\)
hay x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
56 x 52 = 58
1012 x 102 = 1014
23 x 25 = 28
36 x 32 = 38
41 x 46 = 47
67 x 61 = 68
\(5^6\cdot5^2=5^{6+2}=5^8\)
\(10^{12}\cdot10^2=10^{12+2}=10^{14}\)
\(2^3\cdot2^5=2^{3+5}=2^8\)
\(3^6\cdot3^2=3^{6+3}=3^9\)
\(4^1\cdot4^6=4^{1+6}=4^7\)
\(6^7\cdot6^1=6^{1+7}=6^8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5^3\cdot5^5=5^8\)
\(x^4\cdot x=x^5\)
\(6^5:6^2=6^3\)
\(36^3:6^5=6^6:6^5=6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(x-6)2 . (x-6) =64
(x-6)3=64
(x-6)3=43
=>x-6=3
x=9
b)(x+5)3 : (x+5) =144
(x+5)2=144
(x+5)2=122
=>x+5\(\in\left\{12;-12\right\}\)
\(\Rightarrow x\in\left\{7;-17\right\}\)
c)3x+42=196 : (194 . 19)-2.12036
3x+42=196 :195-2
3x+42=19-2
3x+42=17
3x+16=17
3x=1
=>x=0
d)(19x + 2.52) =52 - 42
(19x + 2.52) =25-16
(19x + 2.52) =9
19x + 50 =9
19x = -41
x=\(\frac{-41}{19}\)
tính hợp lí(nếu có thể)
(52004 - 52006):(52005.5)
=(52004 - 52006):52006
=(52004 - 52006).\(\frac{1}{5^{2006}}\)
=\(\frac{5^{2004}}{5^{2006}}\) - 1
=\(\frac{1}{5^2}\) -1
=\(\frac{1}{25}-1=\frac{-24}{25}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
6A = 6 + 62 + ....+ 66
6A - A = (6 - 6) + (62 - 62) + .... + (65 - 65) + 66 - 1
5A = 66 - 1
\(A=\frac{6^6-1}{5}\)
5A + 1 = 66 - 1 + 1 = 66
Vậy x = 6
A=1+6+...+65
6A=6+62+...+66
6A+1=1+6+62+...+66=A+66
6A-A=66-1
5A=66-1
5A+1=66-1+1=66-(1-1)=66
mà 5A+1=6x
nên x=6
Vậy x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
a) = 53+4+1 = 58
b) = 65-4 = 6
c) = 32+3+4-7 = 32
d) = x4+2+1 = x7
e) = 812+10+3 = 825
1. \(5^3.5^4.5=5^{3+4+1}=5^8\)
2. \(6^5:\left(6^3.6\right)=6^5:\left(6^{3+1}\right)=6^5:6^4=6^{5-4}=6^1\)
3. \(\left(3^2.3^3.3^4\right):3^7=\left(3^{2+3+4}\right):3^7=3^9:3^7=3^{9-7}=3^2\)
4. \(x^4.x^2.x=x^{4+2+1}=x^7\)
5. \(\left(8^{12}.8^{10}\right).8^3=8^{12+10+3}=8^{25}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(4510 x 520 ) / 7515=243
(0.8)5 / (0.4)6=0
215 x 94 / 66 x 83=9
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{45^{10}.5^{20}}{75^{15}}=\frac{\left(3^2.5\right)^{10}.5^{20}}{\left(3.5^2\right)^{15}}=\frac{3^{20}.5^{10}.5^{20}}{3^{15}.5^{30}}=\frac{3^{20}.5^{30}}{3^{15}.5^{30}}=3^5=243\)
\(\frac{\left(0,8\right)^5}{\left(0,4\right)^6}=\frac{\left(0,4.2\right)^5}{\left(0,4\right)^6}=\frac{\left(0,4\right)^5.2^5}{\left(0,4\right)^6}=\frac{2^5}{0,4}=\frac{32}{\frac{2}{5}}=32.\frac{5}{2}=80\)
\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=\frac{2^{15}.3^8}{2^{15}.3^6}=3^2=9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5^x+5^{x+1}+5^{x+2}=31.5^6\)
\(\Rightarrow\)\(5^x.\left(1+5^1+5^2\right)=31.5^6\)
\(\Rightarrow\)\(5^x.31=31.5^6\)
\(\Rightarrow\)\(5^x=5^6\)
\(\Rightarrow\)\(x=6\)